“Researcher Saturation”: The Impact of Data Triangulation and Intensive-Research Practices on the Researcher and Qualitative Research Process - Wray, Natalie; Markovic, Milica; Manderson, Lenore (Qualitative health research, 2007)
Theoretically and methodologically sound qualitative research demands an extended period of fieldwork and the use of multiple methods to achieve data saturation and develop the grounded theory. Little is known about the experiences of researchers who conduct such studies. The authors explore these matters by drawing on their experiences of conducting a 3-year qualitative study with women about their gynecological cancer journey. Their fieldwork consisted of participant observation and in-depth interviews with women and health professionals. They demonstrate that researchers who are involved in all phases of emotionally demanding research; that is, data collection (recruiting, observing, expanding field notes, and interviewing), transcription, and data analysis repeatedly relive difficult events, which might potentially compromise the researchers' well-being and, in turn, the research process and data validity. The authors discuss how researchers can deal effectively with these matters during fieldwork and propose a more formal approach to debriefing.